Wastewater Treatment of Shrimp Crackers Industry Using Aerobic Biological by Contact-Stabilization Technology - Ketut Sumada; Cindy Saskia Damayanti; Tiur Lina (Nusantara Science and Technology Proceedings, 2022)
Wastewater from the shrimp cracker industry is produced from the cracker production process from the steam room, washing of raw materials, equipment, production process facilities, and from the steam supply unit that uses coal as an energy source so that it is appropriate for the industry to manage its waste products according to to waste treatment rules in an integrated, efficient, and effective manner. Wastewater of the shrimp cracker industry contains various types of pollutants with levels of Chemical Oxygen Demand (COD) ranging from 916,1 mg/L and Biological Oxygen Demand (BOD) ranging from 431,9 mg/L with a degree of acidity (pH) = 6,0 ±0,4. Increasing the quality of wastewater and decreasing Chemical Oxygen Demand (COD) or Biological Oxygen Demand (BOD) can be done by controlling the F/M ratio which is not yet optimal so that it can be seen the effect of flow rate and the number of microbes on the quality of wastewater from the shrimp cracker industry. Based on the research that has been done, the best results are obtained at a flow rate of 20000 L/day with a significant decrease in BOD and COD, respectively 95,675% and 95,5325%. The quality of the wastewater produced after treatment has a BOD in the amount of 7,928 mg/L and COD in the amount of 16,8 mg/L and this is smaller than the wastewater quality standard BOD in the amount of 50 mg/L and COD in the amount of 120 mg/L.